Public health investments and mortality risk in Brazilian peritoneal dialysis patients - Loesch, Gustavo; Cruz, June A.W.; Pecoits-Filho, Roberto; Figueiredo, Ana E.; Barretti, Pasqual [UNESP]; de Moraes, Thyago P. (Oxford University Press (OUP), 2020)
Background. End-stage kidney disease (ESKD) treatment is very costly and accounts for a significant percentage of public healthcare expenditures. Beyond direct costs, dialysis patients use other healthcare levels, but the impact of public investment on each of these levels is unclear. This study aimed to investigate the association between direct financing at different healthcare levels and overall mortality in peritoneal dialysis (PD) patients. Methods. We included all adult incident PD patients from a Brazilian prospective, nationwide PD cohort. Overall mortality was the primary outcome of interest. We used a three-level multilevel survival analysis to investigate whether mortality was associated with the investments destined to different levels of healthcare complexity: (i) primary, (ii) medium and high and (iii) professional healthcare training and community awareness. Results. We evaluated 5707 incident PD patients from 78 Brazilian cities, which were divided into four quartiles for each healthcare level (Groups I-IV). After taking the highest quartile (Group IV) as a reference, investment in the primary health level was not associated with patient survival. Otherwise, medium and high complexity levels were associated with higher mortality risk. Also, investment in healthcare manager training and community awareness had an impact on patient survival. Conclusions. Investments in different levels of the healthcare system have distinct impacts on PD patient survival. Investment in healthcare manager training and community awareness seems to be a promising strategy on which to focus, given the relatively low cost and positive impact on outcome.
Keywords: Brazilian Unified Health System; BRAZPD; Healthcare levels; Mortality; Peritoneal dialysis; Public investments